1996
DOI: 10.1002/(sici)1097-4660(199601)65:1<45::aid-jctb390>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of aminoglycoside antibiotics with reverse micelles

Abstract: The reverse micelle system of sodium di-2-ethylhexyl phosphate was used to extract aminoglycoside antibiotics, neomycin and gentamicin. The aminoglycosides can be efficiently extracted into a reverse micelle solution, and the antibiotics extracted into the micelle phase can readily be recovered back to a divalent cation aqueous solution, such as Ca2+. The transfer efficiency, %E, is heavily dependent on pH and salt concentration in the aqueous feed solution. %E decreases drastically with pH in the pH range 8.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The results are compared against the experimental results from Mamalis [22] and achieves good results given the coarseness of the mesh -the spread is generally overestimated at higher reductions. Hu et al [120] use this approach to simulate the hot forming of a titanium ring. In this case an elastoplastic material law is used and the guide rolls are modelled to control the roundness of the ring.…”
Section: Metal Forming -Ring Rollingmentioning
confidence: 99%
“…The results are compared against the experimental results from Mamalis [22] and achieves good results given the coarseness of the mesh -the spread is generally overestimated at higher reductions. Hu et al [120] use this approach to simulate the hot forming of a titanium ring. In this case an elastoplastic material law is used and the guide rolls are modelled to control the roundness of the ring.…”
Section: Metal Forming -Ring Rollingmentioning
confidence: 99%
“…However, some highly water-soluble antibiotics (e.g., streptomycin) require ion-exchange separation (Bartels et al, 1958). In addition, a new extraction process based on reverse micelles was recently proposed by Hu and Gulari (1996) for neomycin and gentamycin.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on protein extraction have also shown that pH plays important role in reverse micellar systems [8,12,30,31,[35][36][37][38]. Noble and Varley [39), using protein as the biomolecule, pointed out that the pH of the protein and surfactant solutions could be manipulated so that the protein would exhibit a net charge opposite to that of the surfactant, thus allowing electrostatic interactions between the protein and surfactant in the different phases.…”
Section: Interfacial Association and Phase Volume Changesmentioning
confidence: 99%
“…Separation processes using reverse micelles are based on conventional liquid-liquid extraction techniques. They are easy to scale up, have a high efficiency, can be made selective, have a Iow energy demand, and can be operated continuously [7,8,[10][11][12][13][14]. They can also offer moderate thermal conditions for processing of biomaterials [5,9).…”
Section: Introductionmentioning
confidence: 99%